Enhancing Cancer Immunotherapy: A Novel Approach through the Integration of Oncolytic Virotherapy with CAR-T and NK Cell Therapies - Zhang, Yunan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
A two-pronged approach to fighting cancer, oncolytic virotherapy (OV) combines direct tumor cytotoxicity with potentiation of anti-tumor immunity. Combining OVs and cell therapies, such as CAR-T and NK cells, has been proposed as an enhanced therapeutic approach. Additionally, it has been demonstrated that adding oncolytic virotherapy to combination medicines increases their therapeutic potential. This article explains the mechanisms underlying oncolytic viruses, the beneficial interactions between them and immune cell therapies, as well as the drawbacks and difficulties of this strategy. We highlight the novel approach of combining CAR T/NK cell treatments and oncolytic virotherapy, highlighting current developments and speculating on the future trajectories of this frontier in cancer immunotherapy.